Clinical characterization and further confirmation of the autosomal recessive SLC12A2 disease - Bilal Shamsi, Monis; Saleh, Mohamed; Almuntashri, Makki; Alharby, Essa; Samman, Manar; Peake, Roy W. A.; Al-Fadhli, Fatima M.; Alasmari, Ali; Faqeih, Eissa A.; Almontashiri, Naif A. M. (Journal of human genetics, 2021)
Heterozygous pathogenic variants in SLC12A2 are reported in patients with nonsyndromic hearing loss. Recently, homozygous loss-of-function variants have been reported in two patients with syndromic intellectual disability, with or without hearing loss. However, the clinical and molecular spectrum of SLC12A2 disease has yet to be characterized and confirmed. Using whole-exome sequencing, we detected a homozygous splicing variant in four patients from two independent families with severe developmental delay, microcephaly, respiratory abnormalities, and subtle dysmorphic features, with or without congenital hearing loss. We also reviewed the reported cases with pathogenic variants associated with autosomal dominant and recessive forms of the SLC12A2 disease. About 50% of the cases have syndromic and nonsyndromic congenital hearing loss. All patients harboring the recessive forms of the disease presented with severe global developmental delay. Interestingly, all reported variants are located in the c-terminal domain, suggesting a critical role of this domain for the proper function of the encoded co-transporter protein. In conclusion, our study provides an additional confirmation of the autosomal recessive SLC12A2 disease.